Organic Transistors: Self‐Aligned Megahertz Organic Transistors Solution‐Processed on Plastic (Adv. Electron. Mater. 5/2015). (May 2015) - Higgins, Stuart G.; Muir, Beinn V. O.; Wade, Jessica; Chen, Jiaren; Striedinger, Bernd; Gold, Herbert; Stadlober, Barbara; Caironi, Mario; Kim, Ji‐Seon; Steinke, Joachim H. G.; Campbell, Alasdair J.
<x xml:space="preserve">Abstract</x> The speed of flexible organic field‐effect transistors is limited by both channel length and electrode overlap capacitance; combining nanoimprint lithography with self‐alignment can minimize these factors, yielding high‐frequency devices. The inside cover by A. J. Campbell and co‐workers, based on their article number 1500024, illustrates the fabrication steps of our process, along with a cross‐section (focused ion beam milled scanning electron micrograph) of the resulting transistor.